2009
DOI: 10.1016/j.ejcts.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic post-thoracotomy pain: a critical review of pathogenic mechanisms and strategies for prevention☆

Abstract: Chronic pain complaints after thoracic surgery represent a significant clinical problem in 25-60% of patients. Results from thoracic and other surgical procedures suggest multiple pathogenic mechanisms that include pre-, intra-, and postoperative factors. This review attempts to analyse the methodology and systematics of the studies on the post-thoracotomy pain syndrome (PTPS) after lung cancer surgery in adults, in order to clarify the relative role of possible pathogenic factors and to define future strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
221
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(243 citation statements)
references
References 75 publications
4
221
2
9
Order By: Relevance
“…For example, some studies considered subjects to have PTPS based upon whether pain was present or absent, whereas others required a certain level of pain intensity in order to designate a subject as having PTPS. 9 Many of these investigations involved questionnaires and thus may have been significantly impacted by recall bias. Results from a fairly representative study indicated an overall incidence of 52% (32% mild, 16% moderate, and 3% severe chronic postoperative pain).…”
Section: Incidencementioning
confidence: 99%
See 3 more Smart Citations
“…For example, some studies considered subjects to have PTPS based upon whether pain was present or absent, whereas others required a certain level of pain intensity in order to designate a subject as having PTPS. 9 Many of these investigations involved questionnaires and thus may have been significantly impacted by recall bias. Results from a fairly representative study indicated an overall incidence of 52% (32% mild, 16% moderate, and 3% severe chronic postoperative pain).…”
Section: Incidencementioning
confidence: 99%
“…The degree to which genetics, preoperative pain, and psychosocial factors impact the risk of PTPS is unknown, and more studies are needed to clarify what role, if any, these factors play in the development of PTPS. 9 …”
Section: Preoperative Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-thoracotomy pain syndrome (PTPS) is well established as a clinically important entity after thoracotomy, with persistent pain reported in 30-40% of patients [1]. PTPS is defined by the International Association for Study of Pain (IASP) as 'Pain that recurs or persists along a thoracotomy scar at least 2 months following a surgical procedure' [2].…”
Section: Introductionmentioning
confidence: 99%